East, west : stories - Rushdie, Salman (Pantheon Books, 1994)
In this collection of stories, Salman Rushdie looks at his two worlds: east and west, in their intimacy and distance, their shared history, and the misunderstandings - comic and tragic - that separate and bind them. A rickshaw driver dreams of being a Bombay movie star and Christopher Columbus is an immigrant, dreaming of Western glory.